A biocompatible theranostic nanoplatform based on magnetic gadolinium-chelated polycyclodextrin: in vitro and in vivo studies. (15th February 2021) - Mansouri, Hedieh; Gholibegloo, Elham; Mortezazadeh, Tohid; Yazdi, Mohammad Hossein; Ashouri, Fatemeh; Malekzadeh, Reza; Najafi, Alireza; Foroumadi, Alireza; Khoobi, Mehdi
Graphical abstract: Highlights: A novel theranostic nano-system was designed based on Magnetite decorated with Gd 3+ ions. Novel polycyclodextrin was prepared for Gd 3+ ions chelation and curcumin delivery. The target system showed more toxicity against 4T1 than MCF 10A cells. In vivo anti-tumor study confirmed capability of the system in tumor shrinking without body weight changes. In vitro and in vivo analysis showed efficacy of the system for T1 -T2 dual modality MR imaging. Abstract: A novel theranostic nanoplatform was prepared based on Fe3 O4 nanoparticles (NPs) coated with gadolinium ions decorated-polycyclodextrin (PCD) layer (Fe3 O4 @PCD-Gd) and employed for Curcumin (CUR) loading. The dissolution profile of CUR indicated a pH sensitive release manner. Fe3 O4 @PCD-Gd NPs exhibited no significant toxicity against both normal and cancerous cell lines (MCF 10A and 4T1, respectively); while the CUR-free NPs showed more toxicity against 4T1 than MCF 10A cells. In vivo anticancer study revealed appropriate capability of the system in tumor shrinking with no tissue toxicity and adverse effect on body weight. In vivo MR imaging of BALB/c mouse showed both T1 and T2 contrast enhancement on the tumor cells. Fe3 O4 @PCD-Gd/CUR NPs showed significant features as a promising multifunctional system having appropriate T1 -T2 dual contrast enhancement and therapeutic efficacy in cancer theranostics.